INNOVATION ACTIVITY AND BUSINESS INCUBATORS BASED ON INSTITUTION OF HIGHER EDUCATION. THE EXPERIENCE OF RUSSIA - Romanovich, Liudmila; Evtushenko, Evgeniy; Romanovich, Marina; Кudinov Dmitriy (Journal of Applied Engineering Science, 2015)
Russia, as well as advanced foreign countries, wends the way of innovation-based development. The article describes the economic basis to stimulate innovation activity in the system of small business: current problems and development strategy of science and innovation, the concept of innovation and innovation activities, the criteria of small enterprises, to innovate, as well as questions of the theory and practice of business incubators. The authors analyzed the positive experience of the Belgorod State Technological University named after V.G. Shukhov (Russia, Belgorod) in forming at its base innovative business incubator, carrying out infrastructural support of small innovative enterprises established with the participation of students, graduate students, doctoral students and researchers of the university.